Redox and mTOR-dependent regulation of plasma lamellar calcium influx controls the senescence-associated secretory phenotype. Issue 17 (November 2020) - Chandrasekaran, Akshaya; Lee, May Y; Zhang, Xuexin; Hasan, Shaheen; Desta, Habben; Tenenbaum, Scott A; Melendez, J Andrés
Cellular senescence has evolved as a protective mechanism to arrest growth of cells with oncogenic potential but is accompanied by the often pathologically deleterious senescence-associated secretory phenotype (SASP). Here we demonstrate an H2 O2 -dependent functional disruption controlling senescence-associated Ca 2+ homeostasis and the SASP. Senescent cells fail to respond to H2 O2 -dependent plasma lamellar Ca 2+ entry when compared to pre-senescent cells. Limiting exposure to senescence-associated H2 O2 restores H2 O2 -dependent Ca 2+ entry as well as transient receptor potential cation channel subfamily C member 6 (TRPC6) function. SA-TRPC6 and SASP expression is blocked by restoring Ca 2+ entry with the TRP channel antagonist SKF-96365 or by the mTOR inhibitors rapamycin and Ku0063794. Together, our findings provide compelling evidence that redox and mTOR-mediated regulation of Ca 2+ entry through TRPC6 modulates SASP gene expression and approaches which preserve normal Ca 2+ homeostasis may prove useful in disrupting SASP activity. Impact statement: Through its ability to evoke responses from cells in a paracrine fashion, the senescence-associated secretory phenotype (SASP) has been linked to numerous age-associated disease pathologies including tumor invasion, cardiovascular dysfunction, neuroinflammation, osteoarthritis, and renal disease. Strategies which limit the amplitude and duration of SASP serve to delay age-related degenerative decline. Here we demonstrate that the SASP regulation is linked to shifts in intracellular Ca 2+ homeostasis and strategies which rescue redox-dependent calcium entry including enzymatic H2 O2 scavenging, TRP modulation, or mTOR inhibition block SASP and TRPC6 gene expression. As Ca 2+ is indispensable for secretion from both secretory and non-secretory cells, it is exciting to speculate that the expression of plasma lamellar TRP channels critical for the maintenance of intracellular Ca 2+ homeostasis may be coordinately regulated with the SASP.